Yeast PP4 interacts with ATR homolog Ddc2-Mec1 and regulates checkpoint signaling - Hustedt, Nicole; Seeber, Andrew; Sack, Ragna; Tsai-Pflugfelder, Monika; Bhullar, Bhupinder; Vlaming, Hanneke; van Leeuwen, Fred; Guénolé, Aude; van Attikum, Haico; Srivas, Rohith; Ideker, Trey; Shimada, Kenji; et al. (Molecular cell, 2015)
Mec1-Ddc2 (ATR-ATRIP) controls the DNA damage checkpoint and shows differential cell-cycle regulation in yeast. To find regulators of Mec1-Ddc2, we exploited a mec1 mutant that retains catalytic activity in G2 and recruitment to stalled replication forks, but which is compromised for the intra-S phase checkpoint. Two screens, one for spontaneous survivors and an E-MAP screen for synthetic growth effects, identified loss of PP4 phosphatase, pph3Δ and psy2Δ, as the strongest suppressors of mec1-100 lethality on HU. Restored Rad53 phosphorylation accounts for part, but not all, of the pph3Δ-mediated survival. Phosphoproteomic analysis confirmed that 94% of the mec1-100-compromised targets on HU are PP4 regulated, including a phosphoacceptor site within Mec1 itself, mutation of which confers damage sensitivity. Physical interaction between Pph3 and Mec1, mediated by cofactors Psy2 and Ddc2, is shown biochemically and through FRET in subnuclear repair foci. This establishes a physical and functional Mec1-PP4 unit for regulating the checkpoint response.